#newscrashrecover. (Economist, 2013)
The article looks at the potential effect of social media on securities trading, reporting on the April 2013 temporary stock market crash following a fake news report of explosions injuring U.S. President Barack Obama which was issued by hackers on the microblogging service Twitter.